2008
DOI: 10.4321/s0365-66912008000200004
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomía enzimática por inyección intravítrea de plasmina autóloga como tratamiento inicial del edema macular diabético difuso

Abstract: RESUMENObjetivo: Determinar si la inyección intravítrea de plasmina es efectiva en el tratamiento del edema macular diabético difuso (EMDD). Diseño: Estudio piloto prospectivo, comparativo, de intervención, serie de casos. Pacientes: Dieciocho pacientes con edema macular diabético bilateral, recibieron como primera actuación terapéutica una inyección intravítrea de plasmina en un ojo, sirviendo el ojo contralateral como control. Tratamiento: Inyección intravítrea de 0,2 ml de plasmina autóloga bajo anestesia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
3
0
4
Order By: Relevance
“…In support of the beneficial effect of intravitreal injection of autologous plasmin enzyme (APE), Díaz-Llopis et al12,16 tried to determine the effectiveness of a low-dose intravitreal injection of APE without vitrectomy as a treatment for refractory DDME and reported that intravitreal APE injection effectively reduced macular thickening due to DDME in cases that fail to respond to conventional laser photocoagulation, and improves visual acuity in the short term, and importantly, this result remains stable in the medium term. Sakuma et al17 and Udaondo et al18 evaluated the effects and safety of intravitreal injections of APE, without vitrectomy, as a treatment for macular edema secondary to branch retinal vein occlusion and reported that IAP improves CMT and BCVA and may be a safe and effective alternative therapy for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the beneficial effect of intravitreal injection of autologous plasmin enzyme (APE), Díaz-Llopis et al12,16 tried to determine the effectiveness of a low-dose intravitreal injection of APE without vitrectomy as a treatment for refractory DDME and reported that intravitreal APE injection effectively reduced macular thickening due to DDME in cases that fail to respond to conventional laser photocoagulation, and improves visual acuity in the short term, and importantly, this result remains stable in the medium term. Sakuma et al17 and Udaondo et al18 evaluated the effects and safety of intravitreal injections of APE, without vitrectomy, as a treatment for macular edema secondary to branch retinal vein occlusion and reported that IAP improves CMT and BCVA and may be a safe and effective alternative therapy for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…La plasmina fue preparada en el quirófano inmediatamente antes de la inyección, como ha sido descrita previamente (15,35), con la modificación de sustituir como activador del plasminógeno la estreptoquinasa por la uroquinasa (36)(37)(38)(39)(40). Una muestra de sangre del propio paciente se extrajo de una vena periférica.…”
Section: Preparación De La Plasmina Autólogaunclassified
“…Hasta la actualidad la inyección intravítrea de plasmina se había utilizado siempre inmediatamente antes de la vitrectomía para facilitar el manejo intraoperatorio (16,(27)(28)(29)(30)(31)(32)(33)(34). Recientemente la inyección intravítrea de plasmina autóloga como tratamiento único -sin vitrectomía quirúrgica asociada-ha demostrado ser parcialmente eficaz en el edema macular difuso diabético (35). La eficacia de la inyección aislada de plasmina en conseguir la separación farmacológica del cortex posterior vítreo de la retina, junto con su efecto vitreolítico, conocida como vitrectomía enzimática y vitreolisis farmacológica (16,17,41), abre la posibilidad terapéutica no sólo del edema macular diabético y del STVM, sino de otros edemas maculares (oclusiones venosas, uveítis, postquirúr-gico, etc.)…”
Section: Fig 4: Síndrome De Tracción Vitreomacular (Stvm) Antes (A) unclassified
See 1 more Smart Citation
“…Recientemente diversos autores han publicado un método simplificado, sencillo, barato y rápido de preparación en el propio quirófano de Oftalmología, de manera inmediata antes de la inyección, utilizando como activador enzimático de la plasmina la estreptoquinasa (2,3). Además, dicha técnica resulta muy eficaz como inyección intravítrea única, sin asociar vitrectomía quirúrgica, en los edemas maculares diabéticos tanto como tratamiento inicial como en casos resistentes a toda terapia (láser, trimacinolona y antiVegf intravítreos) antes de intentar la vitrectomía quirúrgica (Díaz-Llopis M et al Intravitreal plasmin without associated-vitrectomy as a treatment for refractory diabetic macular edema.…”
unclassified